A novel gold nanorods coated by stimuli-responsive ABC triblock copolymer for chemotherapy of solid tumors. (June 2019) - Ghamkhari, Aliyeh; Mahmoodzadeh, Farideh; Ghorbani, Marjan; Hamishehkar, Hamed
Graphical abstract: Highlights: A novel gold nanorods-based pH/thermo dual responsive triblock copolymer was developed. The cytotoxicity effect of the GNRs@triblock copolymer-DOX was also confirmed. The obtained results confirmed the potential cell uptake of nanoparticles in comparison to DOX. Abstract: Gold nanoparticles have been used for centuries in medicine for clinical procedures. In this context, gold nanorods are considered as very promising in cancer therapy. For this purpose, gold nanorods (GNRs) coated by stimuli-responsive thiol-end capped ABC triblock copolymer [poly (metacrylic acid)- block -poly ( N -isopropylacrylamide)- block -poly ( N, N -dimethylaminoethyl methacrylate)-SH; P(MAAc- b -NiPAAM- b -DMAEMA)-SH] for intracellular delivery of doxorubicin (DOX). The chemical structures of triblock copolymer were explored by means of Fourier Transform Infrared (FTIR), 1 HNMR spectroscopies and gel permeation chromatography (GPC). The success of coating gold nanorods with triblock copolymer was confirmed by means of ultraviolet–visible (UV–Vis), transmission electron microscopy (TEM), dynamic light scattering (DLS), X-ray powder diffraction (XRD) and thermogravimetric analysis (TGA) measurement. Then, the doxorubicin (DOX)-loading capacity and dual sensitivity drug release ability of the nanocariers (GNRs@triblock copolymer-DOX) were also assessed. The biocompatibility of the prepared nanomaterials was confirmed through the evaluating survival rate of breast cancer cell line (MCF7) using MTT assay. Finally, cellular uptake study and DAPI staining analysis confirmed that nanocarrier successfully improved drugs anticancer activity and the potential of nanocarrier as a bioactive structure. As a result, it is expected that GNRs@tribloc copolymer-DOX may provide promising prospect in the field of nanomedicine mainly due to its biocompatibility and smart physicochemical properties.